2022
DOI: 10.3389/fimmu.2021.797091
|View full text |Cite
|
Sign up to set email alerts
|

Pentose Phosphate Pathway Regulates Tolerogenic Apoptotic Cell Clearance and Immune Tolerance

Abstract: The efficient removal of apoptotic cells (ACs), a process termed as efferocytosis, is essential for immune homeostasis. While recent work has established an important interplay between efferocytosis and cellular metabolic changing, underlying mechanisms remain poorly known. Here, we discovered that pentose phosphate pathway (PPP) regulates tolerogenic ACs clearance and immune tolerance. ACs decreased levels of PPP-related genes and metabolites in macrophages. AG1, the agonist of PPP, increased the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this latter setting, restoration of PPP activity in efferocytic macrophages blunted engulfment of apoptotic cells and stimulated pro-inflammatory cytokine production. 81 Consistent with these findings, a third study, that showed that PPP agonism reduced efferocytosis in vitro and aggravated autoimmune disease in a mouse model of SLE. 82 These findings suggest that PPP flux could be an important…”
Section: The Pentose Phosphate Pathwaymentioning
confidence: 64%
See 1 more Smart Citation
“…In this latter setting, restoration of PPP activity in efferocytic macrophages blunted engulfment of apoptotic cells and stimulated pro-inflammatory cytokine production. 81 Consistent with these findings, a third study, that showed that PPP agonism reduced efferocytosis in vitro and aggravated autoimmune disease in a mouse model of SLE. 82 These findings suggest that PPP flux could be an important…”
Section: The Pentose Phosphate Pathwaymentioning
confidence: 64%
“…While the oxidative phase of PPP was shown to support efferocytosis by generating NADPH in the setting of physiological hypoxia, 80 another study found that efferocytosis decreases PPP flux under normoxic conditions as a result of reduced expression of PPP‐related genes. In this latter setting, restoration of PPP activity in efferocytic macrophages blunted engulfment of apoptotic cells and stimulated pro‐inflammatory cytokine production 81 . Consistent with these findings, a third study, that showed that PPP agonism reduced efferocytosis in vitro and aggravated autoimmune disease in a mouse model of SLE 82 …”
Section: Macrophage Metabolism In Efferocytosis and Resolutionmentioning
confidence: 71%
“…A recent study by He et al (2022) showed that PCM4s downregulate PPP upon efferocytosis. They showed that a PPP agonist, AG1, reduces phagocytosis and enhances the inflammatory phenotype of PCM4s.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being involved in glycolysis, intracellular glucose is involved in the PPP by transforming into glucose 6-phosphate ( 191 ). A previous study suggested that efferocytosis and the PPP are mutually inhibitory ( 192 ). Moreover, a recent study demonstrated that reduced nicotinamide adenine dinucleotide phosphate from the PPP loop contributes to efferocytosis by macrophages under prolonged (chronic) physiological hypoxia ( 193 ).…”
Section: Regulatory Pathways and Molecular Mechanisms Of Efferocytosismentioning
confidence: 99%